Potensi Bahan Baku Dan Proses Pembuatan Terhadap Kualitas Produk Pastry Di Garuda Plaza Hotel - Mida Lishanata Simatupang (Tourism, Hospitality And Culture Insights Journal, 2023)
The purpose of this study is to evaluate the potential of raw materials and production techniques that affect the standard of pastry products at the Garuda Plaza Hotel. High pastry quality is essential to meet client expectations and maintain a competitive advantage in the hospitality sector. Therefore, the raw materials used and the method of making cakes are the two main topics of this research. Quantitative research with an observational approach is the research methodology used. This information was obtained by direct observation of the procedure for making pastry in the hotel kitchen and examining the ingredients used to make the pastry. Garuda Plaza Hotel chefs and cake makers are the research samples. According to the findings of the study, both raw materials and manufacturing procedures have the ability to influence product quality.